Effect of Noise Disturbances on the Response of Measuring Devices - G. M. Alwan; K. T. Rashed (Tikrit Journal of Engineering Sciences, 2008)
The present work studies the effect of noise on the dynamic response of pH, conductivity and thermocouple sensors which used into several industrial processes. Thermocouple would be proven had more stability against noise than conductivity and pH meter. The effect of noise on process signals could be condensate as low as possible by using suitable model of filter especially when the sensors were implemented to a digital computer.